Comparison among research, home, and office blood pressure measurements for pregnant women: The TMM BirThree Cohort Study. Issue 11 (23rd September 2020) - Usuzaki, Takuma; Ishikuro, Mami; Metoki, Hirohito; Murakami, Keiko; Noda, Aoi; Ueno, Fumihiko; Kikuya, Masahiro; Obara, Taku; Kuriyama, Shinichi
Abstract: Blood pressure (BP) measurements of pregnant women have been collected in offices and at home for previous research. However, it remains uncertain whether there is difference between research BP, defined as BP measured for the purpose of epidemiological research and BP measured at home or in an office. Therefore, the present study aimed to compare research BP with home and unstandardized office BP. Research, home, and office BP were measured among pregnant women who participated in the Tohoku Medical Megabank Project Birth and Three‐Generation Cohort Study (TMM BirThree Cohort Study). Research BP was measured twice at our research center while the participant was seated and after resting for 1‐2 minutes. Research, home, and office BP were compared and agreement among the values was assessed. Differences among research, home, and office BP values and possible factors affecting differences were analyzed. Among 656 pregnant women, the mean (± standard deviations) research systolic (S), diastolic (D) BP, home SBP, home DBP office SBP, and office DBP were 103.8 ± 8.5, 61.8 ± 7.3, 104.4 ± 9.2, 61.2 ± 6.8, 110.5 ± 10.8, and 63.8 ± 8.7mmHg, respectively. Research SBP value was lower than home value ( P  = .0072; difference between mean research and home BP: −0.61 ± 7.8 mmHg). Research SBP and DBP values were lower than office values ( P  < .0001 for both SBP and DBP; means ± standard deviations of differences between research and office BP: 6.7 ± 10.1 and 2.0 ± 8.5 mmHg for SBP and DBP, respectively). In conclusion, when research BP is measured under conditions controlled, research BP can give close values to home BP for pregnant women.